The passion of Perpetua and Felicitas in late antiquity - Cobb, L. Stephanie; Jacobs, Andrew S. (University of California Press, 2021)
"This volume gathers all available evidence for the martyrdoms of Perpetua and Felicitas, two Christian women who became, in the centuries after their deaths in 203 CE, revered throughout the Roman world. Whereas they are now known primarily through a popular third-century account, numerous lesser-known texts attest to the profound place they held in the lives of Christians in late antiquity. This book brings together narratives in their original languages with accompanying English translations, including many related entries from calendars, martyrologies, sacramentaries, and chronicles, as well as artistic representations and inscriptions. As a whole, the collection offers readers a robust view of the veneration of Perpetua and Felicitas over the course of six centuries, examining the diverse ways that a third-century Latin tradition was appreciated, appropriated, and transformed as it circulated throughout the late antique world"--